Seasonal dynamics and molecular phylogenetic studies on cercariae in Central Zone of Kashmir valley. - Zahoor Ahmad Wani; Rafiq A Shahardar; Kamal H Bulbul; Idrees M Allaie; Showkat A Shah; Shabir A Rather; Aiman Ashraf; Shahana Tramboo; Asif H Khan (PLoS ONE)
A total of 12103 snails examined in Central Kashmir for determining the population dynamics of cercariae revealed overall prevalence to be 4.03%. Gymnocephalus (0.13%), furcocercous (0.28%), echinostome (0.34%) and xiphido-cercaria (3.26%) were recorded. The prevalence of cercaria was recorded highest in summer (4.28%) followed by spring (4.05%) and autumn (3.32%). None of the cercaria was recorded during winter season. Morphologically identified cercariae of Veterinary importance were subjected to molecular analysis using genus (28S rDNA and ITS-2) specific primers. The isolates of gymnocephalus cercaria (FA28, FC28, FZ28, FC2) were identified as cercarial stages of Fasciola spp. The phylogenetic trees revealed that the isolates FA28 and FC28 belonged to Fasciola gigantica and FZ28 and FC2 isolate to F. hepatica. The isolate of Fasciola gigantica (FA28, FC28, FZ28) showed 2, 4 and 13 nucleotide polymorphisms. There was addition and deletion of 1 and 8 nucleotides at various positions in case of Fasciola isolates respectively. Besides this, there were nucleotide substitutions at 4 positions along with presence of nucleotide T at 475 position which confirmed it be Fasciola hepatica. The isolates of echinostome cercaria (B1, BD13 and GY) were identified as cercarial stages of Moliniella anceps, Echinoparyphium recurvatum and family Echinostomatidae respectively. The Moliniella anceps isolate showed prominent differences at 8 positions with respect to other Echinostomatidae spp. The insertion of C at position 612 confirmed it to be Moliniella anceps, while as other two isolates showed 2 nucleotide polymorphisms each after 28S gene amplification. On ITS-2 rDNA analysis, the isolate B1 showed 7 nucleotide polymorphisms and phylogenetic tree revealed that the isolate B1, also belonged to Echinoparyphium recurvatum. The study made it very clear that molecular characterization employing internal transcribed spacer (ITS-2) and 28S ribosomal DNA sequences are reliable approach for genetic differentiation of cercarial stages of trematodes. The phylogenetic taxonomy of echinostomes is still unclear and molecular diversity found in this study is perhaps the first study from India as well as in Indian subcontinent. So, focus should be made more on echinostomes for understanding their morphological, biological and molecular diversity for clarifying their taxonomic position.